2017
DOI: 10.1016/s0140-6736(17)32032-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of post-partum depression in Palestinian mothers: a cross-sectional study

Abstract: Background Post-partum depression is a major concern for public health that can affects the mother and child. This condition has received little attention in Palestinian primary health care. In this study we aimed to determine the prevalence and associated factors of post-partum depression in women in the Nablus district, occupied Palestinian territory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…According to the findings of the current study, there was no association between any of the sociodemographic factors and PPD. Similar findings were revealed by others (27)(28)30) that there was no significant association between socio-demographic factors namely maternal age, education level of mothers, and working status of mothers and PPD of mothers of neonates admitted to NNICU. However, one study reported that unemployment was associated with PPD (31).…”
Section: Discussionsupporting
confidence: 89%
“…According to the findings of the current study, there was no association between any of the sociodemographic factors and PPD. Similar findings were revealed by others (27)(28)30) that there was no significant association between socio-demographic factors namely maternal age, education level of mothers, and working status of mothers and PPD of mothers of neonates admitted to NNICU. However, one study reported that unemployment was associated with PPD (31).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, they concluded that the Arabic version of the EPDS is a reliable and valid screening tool for depression in postpartum women. The EPDS is widely used in Arab‐speaking countries, such as Jordan and Saudi Arabia (El‐Hachem et al., 2014; Yehia et al., 2013), as well as in Israel (Ayoub et al., 2017; Glasser et al., 2012; Shwartz et al., 2019). All of the studies of PPD in Israeli Arab‐speaking populations have employed the EPDS cut‐off score of ≥ 10 as indicating depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%